Dampak Pemberian Tunjangan terhadap Kinerja Karyawan pada PT. Mitra Agung Swadaya PKS Kelayang Kabupaten Indragiri Hulu - Suharmiyati Suharmiyati; Yenny Iskandar; Reni Maralis (Universitas Batanghari, 2021)
This research was conducted on PT. Mitra Agung Swadaya Pks Kelayang Kabupaten Indragiri Hulu. The purpose of this study was to determine the impact of the provision of allowances on employee performance in PT. Mitra Agung Swadaya Pks Kelayang, Kabupaten Indragiri Hulu. And allowances are part of compensation and compensation is payment in the form of money and / or goods given for achievements and / or awards in a work relationship or after the end of a working relationship based on a structured, open, fair and proper system. Compensation can be in the form of salary or wages, honoraria, allowances, insurance, bonuses, incentives, severance pay, and other forms of compensation. Compensation can. Compensation can be used for 2 (two) basic objectives, namely 1) to attract and retain quality Human Resources and 2) to motivate employees to achieve higher performance levels. The research was conducted using qualitative methods, namely existing data in an organization and quantitative, namely research that describes the impact of providing allowances on employee performance in PT. Mitra Agung Swadaya Pks Kelayang, Kabupaten Indragiri Hulu. By analyzing the data using Instrument Test, Multiple Regression, Correlation Coefficient, Classical Assumption Test and Hypothesis Test which will be assisted by using SPSS version 24. Outputs that are targeted are accredited National Journal Scientific Publications and as teaching materials in Human Resource Management and Management courses Remuneration.